The Effect of Classical Music on Anxiety: A Pre-Post Design - Annisa, Nisrina; Juliawati, Mita (Cakradonya Dental Journal, 2025)
Anxiety is a psychological response often experienced by university students when facing exams, which can affect academic performance. Various factors, such as the exam situation, personal experiences, and physical conditions, can worsen anxiety levels. One intervention that is believed to help reduce anxiety is classical music therapy. This study aims to examine the effect of classical music on the anxiety among students at the Faculty of Dentistry. A pre-experimental study was conducted with 165 students from the 2024 cohort of the Faculty of Dentistry at Universitas Trisakti. The research participants completed the ZSAS questionnaire before and after receiving the classical music intervention. The results showed that he Wilcoxon test yielded p=0.000 (p 0.001), indicating a statistically significant difference between scores before and after the classical music intervention, based on the ZSAS questionnaire. The limitation of this study lies in its participants, who were restricted to a single cohort of students, and in the study design. It can be concluded that classical music has the potential to reduce students anxiety levels.